Trypanosoma congolense infection of trypanotolerant N'Dama (Bos taurus) cattle is associated with decreased secretion of nitric oxide by interferon-gamma-activated monocytes and increased transcription of interleukin-10 - Taylor, K.; Mertens, B.; Lutje, V.; Saya, R. (Wiley, 1998)
The mechanisms whereby trypanotolerant N'Dama cattle control infection with Trypanosoma congolense are unknown. Previous studies have suggested that the monocytes of N'Dama cattle are more highly activated during infection than those of trypanosus ceptible Boan cattle. However, we have recently reported that the monocytes of Boran cattle have a reduced capacity to secrete nitric oxide during trypanosome infection. We therefore evaluated the production of nitric oxide by monocytes of trypanotolerant N'Dama cattle infected with T. congolense in response to interferon-gamma, bacterial lipopolysaccharide or trypanosome anti-gens. Interferon-gamma-induced nitric oxide production was decreased between days 25 and 76 of infection, while lipopolysaccharide-induced secretion of nitric oxide was increased at days 13 and again at day 76 post-infection. Trypanosome antigens did not elicit nitric oxide production. analysis of interleukin-10 mRNA transcription in peripheral blood leucocytes revealed an increase at time points that coincided with decreased interferon-gamma-induced nitric oxide synthesis. In contrast, interferon-gamma mRNA expression was not changed during infection while tumour necrosis factor-alfa was slightly reduced at day 32 post-infection. Recombinant interleukin-10 suppressed interferon-gamma-induced nitric oxide and tumour nmecrosis factor-alpha secretion, but not lipopolysaccharide-induced nitric oxide secretion in cultures of peripheral blood mononuclear cells and monocytes or infected cattle. These results suggest that the nitric oxide response of monocytes to IFN-gamma but not lipopolysaccharide, is suppressed during infection. The kinetics of the upregulation of interlukin-10 and its biological activity indicate a possible association with the depression of nitric oxide production and control of tumour necrosis factor-gamma.